2010
DOI: 10.1021/cn100090g
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine Thioesters as Myelin Proteolipid Protein Analogues to Examine the Role of Butyrylcholinesterase in Myelin Decompaction

Abstract: Multiple sclerosis (MS) is a neuroinflammatory and neurodegenerative disorder involving demyelination, axonal transection, and neuronal loss in the brain. Recent studies have indicated that active MS lesions express elevated levels of butyrylcholinesterase (BuChE). BuChE can hydrolyze a wide variety of esters, including fatty acid esters of protein. Proteolipid protein (PLP), an important transmembrane protein component of myelin, has six cysteine residues acylated, via thioester linkages, with fatty acids, us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…This is supported by the observation that for AChE, like the analogous thiocholine esters, the acetyl ester of N-methyl-4-piperidinethiol (7, Table 1) had the greatest affinity, followed by the propionyl ester (8), while the butyryl derivative (9) was not hydrolyzed by AChE under these conditions. In addition, BuChE affinity increased with longer substrate side chains, consistent with the known preference of this enzyme for longer acyl chains 27,35 . The observation that the thioester analogue of MP4B is BuChE-specific is also in keeping with the earlier report 25 that the ester is only hydrolyzed by BuChE.…”
Section: Kinetic Analysissupporting
confidence: 77%
See 1 more Smart Citation
“…This is supported by the observation that for AChE, like the analogous thiocholine esters, the acetyl ester of N-methyl-4-piperidinethiol (7, Table 1) had the greatest affinity, followed by the propionyl ester (8), while the butyryl derivative (9) was not hydrolyzed by AChE under these conditions. In addition, BuChE affinity increased with longer substrate side chains, consistent with the known preference of this enzyme for longer acyl chains 27,35 . The observation that the thioester analogue of MP4B is BuChE-specific is also in keeping with the earlier report 25 that the ester is only hydrolyzed by BuChE.…”
Section: Kinetic Analysissupporting
confidence: 77%
“…The Ellman spectrophotometric method 26 , or variations thereof 27 , remains the most rapid, reliable and sensitive means to measure AChE or BuChE activity. The principle on which this assay is based is that, thioesters, such as acetylthiocholine and butyrylthiocholine, should be kinetically analogous to their corresponding esters with respect to cholinesterase catalysis.…”
Section: Research Articlementioning
confidence: 99%
“…However, rTMS only normalized the levels of sphingolipids in the hippocampus and PFC. Furthermore, a growing body of evidence indicates that abnormalities in glycerolipid and fatty acyl compositions may also be involved in demyelination ( Sanchez et al, 1998 ; Pottie et al, 2011 ). The present study showed that CPZ treatment decreased glycerolipid levels in both the PFC (DG and MG) and striatum (MG).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, many BChE inhibitors showed capacities to attenuate neuroinflammation. Additionally, in multiple sclerosis, the activation of immune cells microglia would promote the elevation of BChE, 248 and the role of BChE in immune system deserves further studying. In all, the in vivo effects of BChE inhibitors on reversing impaired cognition might not only through elevating ACh, but also through immune response, which is still an understudied field so far.…”
Section: Discussion and Perspectivementioning
confidence: 99%